2014
DOI: 10.4293/jsls.2014.00242
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Drainage Versus No Drainage After Laparoscopic Cholecystectomy

Abstract: Background and Objectives:Routine drainage after laparoscopic cholecystectomy is still controversial. This meta-analysis was performed to assess the role of drains in reducing complications in laparoscopic cholecystectomy.Methods:An electronic search of Medline, Science Citation Index Expanded, Scopus, and the Cochrane Library database from January 1990 to June 2013 was performed to identify randomized clinical trials that compare prophylactic drainage with no drainage in laparoscopic cholecystectomy. The odds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…A recent meta-analysis of 12 randomised controlled trials involving 1939 patients randomised to drain (960) versus no drain (979) demonstrated lower morbidity in the no drain group (OR 1.97 (95% CI 1.26-3.10); P=0.003), lower wound infection (OR 2.35 (95% CI 1.22-4.51); P=0.010), and reduced pain 24 hours postsurgery (Standardised Mean Difference 2.30 (95% CI 1.27-3.34); P<0.0001). However they did not show any difference in the intra-abdominal collections and hospital stay [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 12 randomised controlled trials involving 1939 patients randomised to drain (960) versus no drain (979) demonstrated lower morbidity in the no drain group (OR 1.97 (95% CI 1.26-3.10); P=0.003), lower wound infection (OR 2.35 (95% CI 1.22-4.51); P=0.010), and reduced pain 24 hours postsurgery (Standardised Mean Difference 2.30 (95% CI 1.27-3.34); P<0.0001). However they did not show any difference in the intra-abdominal collections and hospital stay [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drainage does not prevent complications; otherwise, increase the tube-related complications such as fever, wound infection, wound hernia, or discomfort to patients. Furthermore, the recent published randomized controlled trails and and meta-analysis performed by Picchio [ 15 ] and Bugiantella [ 16 ] were both mainly focused on the issue of the role of the drainage in elective or uncomplicated LC and concluded that there was no evidence to support the use of drain after this surgical procedure [ 4 , 5 , 10 ]. However, there are still limited data on the value of prophylactic drains following LC for patients with ACC.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Shamim [13] showed similar ndings. However, study done by Picchio [14] showed 30 ml of mean subhepatic collection in both drain & without drain group. As per many authors, post-cholecystectomy collection in the subhepatic space are on the whole small, rapidly reabsorbed & essentially similar in size & number whether a drain is used or not.…”
Section: Discussionmentioning
confidence: 85%